Analisis Kemampuan Dasar Matematika Upaya Meningkatkan Kualitas Mahasiswa Baru FPMIPA - Lutfiyah Lutfiyah; Dwi Noviani Sulisawati; M Fadil Jamali (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2020)
Analysis of new student registration based on data, that new students of FPMIPA IKIP PGRI Jember in many registration forms dropped first choice in biology education study program and second choice in other faculties, based on that matter is an evaluation material that must be done by FPMIPA whether students new students who choose biology education study programs also have good basic math skills with the aim of improving the quality of new student admissions at FPMIPA, so it needs to be analyzed about the basic mathematical abilities possessed by new students who are in FPMIPA Especially new students of biology education study programs. The formulation of the problem in this case, is how to analyze the basic abilities of mathematics to improve the quality of new students of FPMIPA, with the aim is to find out the results of the analysis of the basic mathematical abilities of new students of FPMIPA to improve the quality of FPMIPA new student admissions each year. Descriptive qualitative research design with 6 research subjects, the results of the study that the structure of solving mathematical problems that are owned by new students of biology education study programs, 4 subjects have basic mathematical abilities. The study concludes that new students of FPMIPA who have an interest in choosing biology education study programs also have basic mathematical abilities, which is an effort to improve the quality of new student admissions at FPMIPA.